(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In modern state educational policy, the priority of the personality of the subject and object of education is proclaimed; criteria of the modern personality are formed, among which the most important are spirituality, comprehensive development, healthy interests and needs (especially cognitive, value-oriented, intellectual and creative, self-educational, self-actualization and self-realization).